Educación financiera con enfoque de género en Instituciones educativas del sistema privado - Acaro Camacho, Ginger Salome (2023)
The general objective of this research project, called financial education with a gender approach in private educational institutions, is to evaluate the relationship between the financial education variable and the demographic variable gender in private educational centers. To meet the objective, a survey was applied to 302 students from 4 educational institutions in the city of Loja in order to characterize the financial knowledge profile of young people, resulting in students at a level 4 of financial knowledge as established by the PISA methodology, that is to say they are able to interpret how the management of bank accounts works, compound interest and analysis of less common financial products, on the other hand, The relationship between the financial education variables and the demographic variable gender was analyzed through the parametric chi-square test, obtaining as a result an asymptotic significance value of 0.479, which is greater than 0.05, allowing the acceptance of the null hypothesis which mentions that there is no relationship between them, that is to say that regardless of gender, students have high levels of financial education, within this research it can be evidenced that there are more men in these educational centers. Finally, with the data obtained from the research, we propose the design of a podcast channel where the necessary contents are found to strengthen and expand their level of financial knowledge, thus adapting to the use of ICTs.